Characterizing the Rise of Disseminated Gonococcal Infections in California, July 2020–July 2021. (3rd October 2022) - Tang, Eric C; Johnson, Kelly A; Alvarado, Lizzete; Burghardt, Nicole O; Hernandez, Cindy; Lopez, Edwin; Jenkins-Barnes, Tazima; Hughes, Bryan; Salas, Krysta L; Jacobson, Kathleen R
Abstract: Background: California has experienced an increase in reported cases of disseminated gonococcal infection (DGI). Given significant morbidity associated with DGI and the ability of Neisseria gonorrhoeae to rapidly develop antibiotic resistance, characterization of these cases can inform diagnosis, management, and prevention of DGI. Methods: As part of the public health response to increased reports of DGI, we used gonorrhea surveillance data reported to the California Department of Public Health to identify all DGI cases in a geographically-bound region. Standardized case report forms were used to collect epidemiologic risk factors and clinical information obtained from provider/laboratory reports, medical records, and patient interviews. Results: From 1 July 2020 to 31 July 2021, we identified 149 DGI patients among 63 338 total gonorrhea infections, representing 0.24% of gonorrhea cases. Estimated incidence was 0.47 DGI cases per 100 000 person-years. Mean age of DGI patients was 40 years, and 75 (50%) were cisgender men, of whom only 13 were known to have male partners. Where reported, more than one-third (36%) used methamphetamine and nearly one-quarter (23%) experienced homelessness. Clinically, 61% lacked urogenital, pharyngeal, or rectal symptoms; 2 patients died in the hospital. Among 47 isolates from patients with antimicrobial susceptibility testing (AST) results available, all were susceptible to ceftriaxone and cefixime. Conclusions: Most DGI patients lacked urogenital symptoms and were not among populations for which routine gonorrhea screening is currently recommended. Expanding gonorrhea screening might prevent DGI. Cefixime is likely the best option if transitioning from parenteral to oral therapy when AST results are unavailable. Abstract : A total of 149 disseminated gonococcal infection (DGI) cases in California were identified; most were aged ≥40 years, heterosexual, or did not present with urogenital symptoms. All isolates with reported results were susceptible to ceftriaxone and cefixime. Expanding gonorrhea screening may prevent DGI.